NAVIGATING INDONESIA’S BLUE ECONOMY: LESSONS LEARNED FROM LITERATURE (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
This paper explores the connection between American literature and environmental issues, focusing on greed and pollution. It analyzes Jack London’s The Sea Wolf to understand how it can highlight the negative effects of unchecked greed on natural resources. The findings can help Indonesia manage its marine resources. By understanding the dangers of greed and pollution, Indonesia can develop a sustainable approach to its ocean resources. From the perspective of Jesuit ecological justice, which emphasizes the preservation of delicate ecosystems and moral resource management, the exploitation of life in the ocean is abhorrent. The study suggests that literature can inform policy discourse and promote environmental stewardship in the Blue Economy context. The implications include promoting ecological awareness, interdisciplinary research, and leveraging literature for positive social and environmental change.
Keywords: blue economy; overfishing; ecosystem